toxB Gene on pO157 of Enterohemorrhagic Escherichia coli O157:H7 Is Required for Full Epithelial Cell Adherence Phenotype - Tatsuno, Ichiro (American Society for Microbiology, 2001)
Adherence of enterohemorrhagic Escherichia coli (EHEC) to the intestinal epithelium is critical for initiation of a bacterial infection. An in vitro infection study previously indicated that EHEC bacteria initially adhere diffusely and then proliferate to develop MC, a process that is mediated by various secreted proteins, such as EspA, EspB, EspD, Tir, and intimin, as well as other putative adherence factors. In the present study, we investigated the role of a large 93-kb plasmid (pO157) in the adherence of O157:H7 (O157Sakai) and found the toxB gene to be involved in the full adherence phenotype. A pO157-cured strain of O157Sakai (O157Cu) developed microcolonies on Caco-2 cells; however, the number of microcolonies was lower than that of O157Sakai, as were the production and secretion levels of EspA, EspB, and Tir. Introduction of a mini-pO157 plasmid (pIC37) composed of the toxB and ori regions restored full adherence capacity to O157Cu, including production and secretion of the proteins. In contrast, introduction of a pO157 mutant possessing toxB::Km into O157Cu could not restore the full adherence phenotype. Expression of truncated versions of His-tagged ToxB also promoted EspB production and/or secretion by O157Cu. These results suggest that ToxB contributes to the adherence of EHEC to epithelial cells through promotion of the production and/or secretion of type III secreted proteins.